Analysis of the Application of Criminal Law to Corporations Dumping Hazardous Waste into Environmental Media in the Supreme Court Decision (No. 1405/K/Pid.Sus./2013) - Mikael Gomgom Marisi Sihombing; Alvi Syahrin; Suhaidi Suhaidi; Mahmud Mulyadi (Inspiring Law Journal, 2025)
Environmental arrangements are regulated in Law No. 32 of 2009 concerning Protection and Management of the Environment. Corporation is a body created by law. The body that is created consists of "corpus" which is its physical structure and in it the law includes an element of "animus" that makes the body and the law is a legal creation then except the creator, his death is also determined by law. The regulation of criminal responsibility and individual responsibility for corporations and corporate administrators as perpetrators of criminal acts is regulated in Law No. 32 of 2009 concerning the protection and management of living environments. To find out who the criminal offender in the environment can be used as proof theory so that directing information can be found in the company. The research used in this legal research is normative law. Normative legal research or also called library legal research is legal research conducted by examining library materials or mere secondary data.